DINAMIKA HISAB RUKYAT DI INDONESIA - Ahmad Izzuddin (Institut Agama Islam Negeri Metro, 2015)
Rukyat reckoning in Indonesia synonymous with crucial endless conflict. Determination loaded with the beginning of the month of Ramadan phenomenon of determination dated 1 Shawwal and Dzulhijah. Determination early in the calendar hijriyah Typically, the difference was the case of the methods used. To determine 1 Ramadan could Rukyat and Hisab. Each one has a proposition. So if it is different, but there are strong arguments. Hilal debate current hot issue ahead of the fasting month and 1 Shawwal. Hilal is the earliest appearance in the visible faces of the earth after months of conjunctions / ijtimak. This initial month will appear on the western horizon (maghrib) at sunset. Ijtimak / conjunctions are events that occur when the angular distance (elongation) of an object with another object is equal to zero degrees. In the approach to astronomy, Conjunction is an event when the sun and moon are aligned in the same plane of the ecliptic. At a certain moment, these conjunctions can cause a solar eclipse. Hilal is the criteria for an initial month. As we know, in the Hijri calendar, a day starting from sunset local time, and the determination of the beginning of the month (calendar) depending on the sighting of the new moon / month. Therefore, the Islamic calendar month can be aged 29 days or 30 days. Rukyat visibility of the new moon is observed activity, namely sighting the crescent first appears after the ijtimak. Rukyat can be done with the naked eye, or with optical aids such as telescopes. Rukyat activity carried out on the eve of the first sunset after ijtimak (at this time, the position of the moon is on the western horizon, and the moon sets shortly after sunset). When the moon is visible, then in the evening local time has been entered date 1. In addition to the new moon and rukyat term reckoning still controversy. Hisab often used as an astronomical mathematical calculation method to estimate the position of the sun and moon to the earth. Determination of the position of the sun is important because Muslims to worship prayers using the sun's position as the benchmark prayers. While the determination of the position of the moon to know the moon to mark the entry of the new moon period in the Hijri calendar.